Effects of Providing Enrichment to Broilers in an Animal Welfare Environment on Productivity, Litter Moisture, Gas Concentration (CO2 and NH3), Animal Welfare Indicators, and Stress Level Concentration - Chan-Ho Kim; Woo-Do Lee; Ji-Seon Son; Jung-Hwan Jeon; Se-Jin Lim; Su-Mi Kim (Agriculture)
As animal welfare becomes more active in livestock industry, research is being conducted on ways to improve poor housing environments, reduce stress, and meet welfare standards. Among these, environmental enrichment methods are effective in reducing stress and creating a welfare-friendly rearing environment, but there are few cases of actual application to farms. Therefore, we aimed to investigate the effect of providing pecking materials (grain blocks), known as one of the environmental enrichment methods, to commercial broiler farms. This study used two facilities that could accommodate 32,000 one-day-old broilers (Arbor acres) per building, and two groups (control and treatment groups) were designed after creating two identical areas within each building (total two treatments, two replicates, 16,000 birds per replicate). Two identical zones within the house were created by installing a partition in the center; one side was provided with grain blocks (one grain block per 1000 birds), and the other side was not. Analysis items included productivity (body weight, uniformity), environmental variables (litter and air), welfare indicators (leg, gait score, feather cleanliness score), and serum corticosterone levels. Analysis of all items was conducted twice, on the 19th and 27th, taking into account the farm’s feed change date and slaughter schedule. Other environmental conditions (density, lighting, ventilation, temperature, humidity, feed, and water) were the same. As a result, no difference in productivity was observed according to enrichment, and the quality of litter and air was similar. Also, there was no significant difference in welfare indicators. Interestingly, however, provision of the environment enrichment lowered serum corticosterone levels (p < 0.05). The implications of our study are that grain blocks as a pecking material are an effective way to reduce stress without adversely affecting broiler performance and rearing environment. However, it is still necessary to explore optimal enrichment materials that can help not only the welfare level but also the broiler performance.